PAULO FREIRE AND THE COUNTRYSIDE EDUCATION – PARADIGMATIC UPDATES - Wellington Amancio da Silva; Juracy Marques dos Santos (European Scientific Journal, ESJ, 2014)
The present article aims at analyzing the educational contributions, political, economic, ideological and sociocultural pedagogical thinking of Paulo Freire in the education field. For it made a succinct historical and cultural relationship between Brazilian ideological political context, the late 30 until the military dictatorship of 1964 and the current education, especially in the perspective of the field to what Paulo Freire began his contributions.